The joy and pain of being a harm reduction worker: a qualitative study of the meanings about harm reduction in Brazil - João Maurício Gimenes Pedroso; Cristiana Nelise de Paula Araujo; Clarissa Mendonça Corradi-Webster (BMC, 2024)
Abstract Background Although harm reduction is highlighted as an effective intervention for alcohol and drug use, a funding gap for harm reduction interventions has been identified, mainly in low- and middle-income countries. In these countries, tensions between abstinence and harm reduction models have impaired the shift from punitive practices to evidence-based interventions committed to guaranteeing the human rights of people who use drugs. Since 2015, the Brazilian government has adopted a more punitive and abstinence-focused drug policy that jeopardizes the care of people who use alcohol and other drugs and the comprehension of the harm reduction workers' perspective in relation to their practice. Therefore, this study aimed to comprehend the meanings constructed by Brazilian harm reduction workers regarding their practices with vulnerable populations amidst a context of political tension. Methods We conducted 15 in-depth semi-structured qualitative interviews with harm reduction workers employed in public health services for at least 6 months. Data were analyzed using thematic analysis. Results The thematic axis "The joy and pain of being a harm reduction worker in Brazil" was constructed and divided into four major themes: (1) Invisibility of harm reduction work; (2) Black, poor, and people who use drugs: identification with the service users; (3) Between advocacy and profession: harm reduction as a political act; (4) Small achievements matter. Despite the perceived invisibility of harm reduction workers in the public health and alcohol and drug fields, valuing small achievements and advocacy were important resources to deal with political tension and punitive strategies in Brazil. The findings also highlight the important role of harm reduction workers due to their personal characteristics and understanding of drug use behavior, which bring the target audience closer to actions within the public health system. Conclusion There is an urgent need to acknowledge harm reduction based on peer support as a professional category that deserves adequate financial support and workplace benefits. Additionally, expanding evidence-based harm reduction interventions and community-based voluntary drug use treatment centers should be prioritized by public policies to address the human rights violations experienced by people who use drugs.